The Utilization of Specialist Palliative Care and Other Health Care Services at the End of Life Among Patients with Head and Neck Cancer: A Nationwide Cohort Study - Merikari, Martti; Akrén, Outi; Nuutinen, Mikko; Mäkitie, Antti; Saarto, Tiina; Carpén, Timo (Springer Science and Business Media LLC, 2025)
Introduction: The end of life of patients with head and neck cancer (HNC) is plagued by significant morbidity and high symptom burden, emphasizing the need for palliative care. Our aim was to evaluate the utilization of health care services, including specialist palliative care (SPC), among patients with HNC at the end of life. In addition, we wanted to explore the timing of SPC contact on the utilization of health care services at the end of life.
Methods: The study population consisted of all 281 patients who died of HNC in 2019 in Finland. Data were collected from nationwide registries. Patients were divided into two groups according to the timing of their first contact with an SPC unit: early (> 30 days before death), and late/no (≤ 30 days before death or no contact).
Results: Mean age at death was 72 years, and 66% were male. The hospital was the most common place of death (82%). Ninety-three (33%) patients had contact with an SPC unit, and the median time of the first SPC contact was 62 days before death. Comparing those with early and late/no SPC contact, the early group was significantly associated with lower secondary health care hospitalization (31% vs. 53%; p = 0.002) and emergency care utilization (33% vs. 52%; p = 0.006) during the last month of life. The early SPC group was also associated with higher utilization of home care (52% vs. 36%; p = 0.021), SPC outpatient clinic (24% vs. 5%; p < 0.001), SPC ward (22% vs. 4%; p < 0.001), and palliative hospital-at-home services (45% vs. 5%; p < 0.001) during the last month of life. Among patients with the early SPC contact, SPC ward was significantly more likely to be the place of death (18% vs. 4%, p < 0.001) compared with patients with late/no SPC contact.
Conclusion: Patients with HNC utilize health care services at high rates at the end of life. Early SPC contact is associated with increased SPC service use and decreased utilization of secondary health care and emergency care, highlighting the need for early and greater access to SPC services for patients with HNC.
Keywords: End of life; Head and neck cancer; Health care utilization; Palliative care; Specialist palliative care.